2013
DOI: 10.1111/1744-9987.12055
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Ankle‐Brachial Index Decline Predicts Cardiovascular Mortality in Hemodialysis Patients

Abstract: Chronic kidney disease is a risk factor for cardiovascular mortality and morbidity of cardiovascular events (CVEs). We obtained baseline data regarding blood biochemistry, ankle-brachial index (ABI), brachial-ankle pulse wave velocity (baPWV) and echocardiographic parameters from 300 patients on hemodialysis in 2005. We also measured ABI and baPWV annually from June 2005 until June 2012 and calculated rates of changes in ABI and baPWV to identify factors associated with CVEs. Seventy-three patients died of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…We also confirmed that a low ABI was a risk factor for mortality. Recently, Kuwahara et al estimated 300 hemodialysis patients and showed that a higher rate of ABI decline was a prominent predictor of survival among patients receiving hemodialysis therapy (HR, 4.044; P < 0.001 [per 0.1/year decrease]) in multivariate Cox analysis [11]. We also showed that the change in the ABI was a risk factor for mortality, but it was a univariate analysis because of the small sample size.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We also confirmed that a low ABI was a risk factor for mortality. Recently, Kuwahara et al estimated 300 hemodialysis patients and showed that a higher rate of ABI decline was a prominent predictor of survival among patients receiving hemodialysis therapy (HR, 4.044; P < 0.001 [per 0.1/year decrease]) in multivariate Cox analysis [11]. We also showed that the change in the ABI was a risk factor for mortality, but it was a univariate analysis because of the small sample size.…”
Section: Discussionmentioning
confidence: 55%
“…Clinically, the anklebrachial blood pressure index (ABI) is highly correlated with PAD of the lower extremities [10], and ABI is an independent predictor of all-cause mortality in hemodialysis patients [6][7][8][9]. A recent study also revealed that not only the value of the ABI itself but also the rate of the reduction in the ABI was a risk factor for cardiovascular mortality [11]. In the present study, we investigated the effect of changes in the ABI on mortality and the factors that predict changes in the ABI in hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…A low ABI has been reported to be a reliable diagnostic marker for PAOD with high sensitivity and specificity, and also to be a strong predictor for overall and cardiovascular mortality in HD patients345. We also previously reported an association between a low ABI and vascular access failure6.…”
mentioning
confidence: 73%
“…In this context, the ankle brachial pressure index ABI is particularly useful in functionally evaluating peripheral arterial disease, and the rate of ABI decline predicts cardiovascular mortality in HD patients 26 . Previously, we used this index in comparing a cohort of 20 HD patients after 2 years of linagliptin treatment the linagliptin group with 20 HD patients with diabetes who received once-daily doses of 6.25 mg alogliptin the alogliptin group .…”
Section: Discussionmentioning
confidence: 99%